ANALISIS MUSIK IRINGAN TARI LANGKAH JEPIN PENGHIBUR PENGANTIN DI PONTIANAK KALIMANTAN BARAT - Septia Widya, Upik Riska; Syahrani, Agus; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractOne of the traditional arts of Malayan ethnic in Pontianak, West Kalimantan is the music of Jepin Langkah Penghibur Pengantin Dance. The problem formulations in this research were, 1) How is the musical analysis of Jepin Langkah Penghibur Pengantin dance in Pontianak, West Kalimantan, 2) How is the melodic structure of Pantun Penganten poem vocals in Pontianak, West Kalimantan. The method used in this research was descriptive qualitative method with musicology approach. The data contained in this study were the result of direct observation and interviews to informants in the shape of musical form and melodies of Jepin Langkah Penghibur Pengantin Dance. The data were analyzed qualitatively, with Yusuf Dahyani, Anwar Djafar and Juhermi Thahir as the informants, and other art actors who have an active role and know about the music of Jepin Langkah Penghibur Pengantin Dance in Pontianak, West Kalimantan. Based on the data analysis, researcher concluded that the music of Jepin Langkah Penghibur Pengantin Dance has one part, six phrases, and eleven motives. Based on the analysis of vocal music in Pantun Penganten poem, there are three analyzes that is by ornamentation, not with ornamentation and analysis of vocal melodic motives.Â Keywords: Analysis, Music of Jepin Langkah Penghibur Pengantin Dance, Malayan ethnic, Pontianak, West Kalimantan.